Fabrication of sinter-free conductive Cu paste using sub-10 nm copper nanoparticles. Issue 47 (24th November 2017) - Lee, Jungsup; Jun, Jaemoon; Na, Wonjoo; Oh, Jungkyun; Kim, Yunki; Kim, Wooyoung; Jang, Jyongsik
Abstract : Fabrication procedure of conductive Cu NP paste using sub-10 nm copper nanoparticles for excellent conductivity without heat treatment. Abstract : We herein describe the fabrication of sinter-free copper nanoparticle-based conductive paste (Cu NP paste). The copper nanoparticles with a size below 10 nm enable the formation of integrated structures even without heat treatment. Poly(vinylimidazole- co -vinyltrimethoxysilane) used in the synthesis grants the copper surface a high anti-oxidant ability over a temperature range of up to 300 °C under ambient conditions. Furthermore, the viscosity of the conductive paste could be arbitrarily adjusted while minimizing the change of resistivity. The pattern printed using Cu NP paste demonstrated an electrical resistivity of 1.2 × 10 −2 Ω cm for un-sintered conductive paste. We confirmed the potential of the Cu NP paste through dipole tag antenna application.